The Leran Site Eksistensi Situs Leran di Gresik - Rahardi Teguh Prakoso (LP4MK STKIP PGRI Lubuklinggau, 2021)
Leran site is a historical relic that has been evidence of the spread of Islam since the 11th century in Nusantara. This is based on the evidence of inscriptions that are found in addition to the tomb of Nyai Swari or better known as Fatimah binti Maimun. In the inscription is listed about the year that indicates the age of the tomb. However, there are still so many opinions on the inscription beside the Nyai Swari tomb. Nyai Swari itself is one of the leaders of Islamic religious people in the region. In general, the site consists of three burial complexes, namely the tomb of Fatimah Binti Maimun, a long grave complex, the ancient cemetery complex of local people. Each tomb lies not so far from each other. The differentiator of the complex also has a complex with fences and gates. The tomb, which has a fence and gate of the buildings, is an important person in the complex. The more magnificent gate of the buildings owned by a tomb, then the higher the strata that have a character who dwell in the tomb. The significance of the tomb is a tomb or graveyard made to commemorate or honor the greatness of the name of one who has long ago died and was buried in certain burial areas in an area. Around the tomb of these important figures erected a house that is very beautiful architecture called a cup or dome, serves as a place to put the offerings to pay homage to the people buried in the place.